PERANAN DESA ADAT DALAM MENERAPKAN SANKSI TERHADAP PELANGGARAN PROSES PERKAWINAN DALAMAWIG-AWIG DESA ADAT DI DESA ADAT TAKMUNG KECAMATAN BANJARANGKAN KABUPATEN KLUNGKUNG - Trinaya Dewi, A.A. Mas Adi; Dewi, Ni Made Trisna; Listya Dewi, Ni Putu (Kerta Dyatmika, 2024)
The Customary Village as a legal community unit in Bali Province has a unity of tradition and manners of social life of the Hindu community that has been passed down from generation to generation in the Kahyangan Tiga (Kahyangan Village) bond which has its own territory and wealth and has the right to manage its own household. As a legal community unit (Customary Village) is bound by Customary rules or Customary laws that grow and develop in the local community environment, which is better known in the form of Awig-Awig which is the basic guideline of the Customary Village in its governance. The purpose of this study is to determine the application of sanctions for the Customary Village awig-awig and what obstacles are experienced in relation to marital violations committed by the Krama of the Takmung Customary Village. The approach method used is an empirical approach, to be able to provide a qualitative picture. Primary and secondary data are conducted through library and field research with document studies and interview guidelines. The conclusion of this study shows that the application of sanctions for violations of customary village laws depends on the violations committed in accordance with what is stated in the customary village laws of Takmung by prioritizing amicable and wise resolution, either in the form of physical fines or fines with property (material). With continuous socialization to village residents and firm action from both village officials and the compliance of village residents, obstacles in the application of sanctions can be resolved as well as possible.